Spin-off firms and individual start-ups. Are they really different? - Sierdjan Koster (European Regional Science Association (ERSA), 2004)
In the field of firm demography, spin-offs have recently attracted attention as a very successful form of new firm formation. Policy makers see spin-offs as particularly fertile innovators in an economy. Theoretically, following lines of thought from the resource-based theory, spin-offs are also expected to perform better than other start-ups that lack the resource base spin-offs inherited from their mother companies. This paper shows, based on an empirical study of American entrepreneurs (ERC-dataset) that spin-offs are indeed a step ahead of firms that do not receive support from a third party company. In the early stages of their existence, spin-offs are leading other new firms in the development of their products, spin-offs show an increased tendency to hire personnel, and spin-offs receive their first income sooner than other firms. At start-up, spin-outs hardly differ from individual start-ups, which have not received any back-up during the gestation process. After one year they seem to perform slightly better.
Keywords: 330